Enhancing Community Economy through a New Value Chain of Red Tilapia in Lum Nam Nan, Uttaradit Province, Thailand - Sakunphun, Sriprai; Uppapong, Kullaya; Junkawee, Tulaporn; Palas, Piyawan; Roonreangjai, Rueankhwan (Area Based Development Research Journal, 2024)
Uttaradit province of Thailand produces and sells an average of 3,437.15 tons of red tilapia annually, which is insufficient to meet market demand. The existing value chain comprises only production and collection. Major challenges faced by producers include the high cost of fish feed, the inability of small-scale farmers to select quality fish breeds, and a lack of effective farm management knowledge. This research focuses on enhancing the red tilapia value chain through a collaborative network involving two hatcheries, six production businesses, the Uttaradit Aquaculture Cooperative, and one collection business. The interventions include: 1) participatory attitude adjustments to raise awareness about production record-keeping, 2) planning for production inputs and developing the farming process based on the “4 Good” production system-good breed, good feed, good farm management, and good marketing, and 3) business strategy development, including backward integration by expanding value chain links into input supply processes, and forward integration through joint marketing planning with collection businesses to boost sales and promote local consumption. Through knowledge exchange, capacity building, and practical experiments, the income of hatchery businesses increased by 27.93%, production businesses saw a 41.74% rise in revenue, with profits increasing by 5,000–10,000 THB (around 147-294 USD) per cage. Employment was created for 165 people, and new roles such as red tilapia hatchery operators, primary processors, processors, and sellers. Retail businesses achieved the highest value increase of 20%, collection businesses saw a 12.26% increase, and wholesale fresh fish businesses experienced a 10.53% increase. This distribution of income and benefits throughout the value chain positively impacted the community economically and socially.